Turbulent forced convection flow of nanofluids over triple forward facing step - Hashim N.M.R.; Yusoff M.Z.; Mohammed H.A. (Emerald Group Publishing Ltd., 2023)
Purpose - The purpose of this paper is to numerically study the phenomenon of separation and subsequent reattachment that happens due to a sudden contraction or expansion in flow geometry, in addition, to investigating the effect of nanoparticles suspended in water on heat transfer enhancement and fluid flow characteristics. Design/methodology/approach - Turbulent forced convection flow over triple forward facing step (FFS) in a duct is numerically studied by using different types of nanofluids. Finite volume method is employed to carry out the numerical investigations. with nanoparticles volume fraction in the range of 1-4 per cent and nanoparticles diameter in the range 30-75 nm, suspended in water. Several parameters were studied, such as the geometrical specification (different step heights), boundary conditions (different Reynolds [Re] numbers), types of fluids (base fluid with different types of nanoparticles), nanoparticle concentration (different volume fractions) and nanoparticle size. Findings - The numerical results indicate that the Nusselt number increases as the volume fraction increases, but it decreases as the diameter of the nanoparticles of nanofluids increases. The turbulent kinetic energy and its dissipation rate increase as Re number increases. The velocity magnitude increases as the density of nanofluids decreases. No significant effect of increasing the three steps heights on Nusselt along the heated wall, except in front of first step where increasing the first step height leads to an increase in the recirculation zone size adjacent to it. Research limitations/implications - The phenomenon of separation and subsequent reattachment happened due to a sudden contraction or expansion in flow geometry, such as forward facing and backward facing steps, respectively, can be recognized in many engineering applications where heat transfer enhancement is required. Some examples include cooling systems for electronic equipment, heat exchanger, diffusers and chemical process. Understanding the concept of these devices is very important from the engineering point of view. Originality/value - Convective heat transfer can be enhanced passively by changing flow geometry, boundary conditions, the traditional fluids or by enhancing thermal conductivity of the fluid. Great attention has been paid to increase the thermal conductivity of base fluid by suspending nano-, micro-or larger-sized particles in fluid. The products from suspending these particles in the base fluid are called nanofluids. Many studies have been conducted to investigate the heat transfer and fluid flow characteristics over FFS. This study is the first where nanofluids are employed as working fluids for flow over triple FFS. Emerald Publishing Limited.